2006
DOI: 10.1068/b32082
|View full text |Cite
|
Sign up to set email alerts
|

Space Syntax Analysis of Colonial Houses in India

Abstract: The influence of colonial (British) rule on native (Indian) culture and vice versa has resulted in the development of ‘hybrid’ architectural styles, which are seen in the external ‘form’ of the buildings. The development of a hybrid style is an important phase in the evolution of domestic architecture in India. In this paper we explore whether such hybrid nature is also reflected in the spatial organizations of some colonial houses of eastern India. For this, a suitable methodology was evolved to analyze the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…10 Since then, a substantial amount of research on domestic space has been carried out in different parts of the world using this analytical framework. Valuable examples of this are the study of houses of Chaco Canyon in New Mexico (Bustard, 1999), the evolution of domestic architecture in India through the analysis of houses with English influence (Bandyopadhyay and Merchant, 2006), the modern houses in Recife (Amorim, 1999), or the apartment buildings in Brasília (França and Holanda, 2009) in Brazil. The focus of all of these studies was a search for genotypes.…”
Section: Methodsmentioning
confidence: 99%
“…10 Since then, a substantial amount of research on domestic space has been carried out in different parts of the world using this analytical framework. Valuable examples of this are the study of houses of Chaco Canyon in New Mexico (Bustard, 1999), the evolution of domestic architecture in India through the analysis of houses with English influence (Bandyopadhyay and Merchant, 2006), the modern houses in Recife (Amorim, 1999), or the apartment buildings in Brasília (França and Holanda, 2009) in Brazil. The focus of all of these studies was a search for genotypes.…”
Section: Methodsmentioning
confidence: 99%
“…Also, Dursun and Saglamer (2003) used Space Syntax techniques to study the various spatial patterns in terms of the similarities and differences between different home environments which have been formed through the history of Trabzon, Turkey. Bandyopadhyay and Merchant (2006) studied the influence of British-Indian hybrid architectural styles on the spatial organization of houses in Eastern India. The study suggested that a consistent pattern was observed in the RRA values.…”
Section: Applications Of Space Syntax Theorymentioning
confidence: 99%
“…Furthermore, the space syntax theory has been used as a viable tool to study the functional performance of a variety of building layouts such as worship centers (Mustafa and Hassan, 2013), historical sites and buildings (Li et al, 2016), shopping malls (Al-Juboori and Mustafa, 2014), home environments (Dursun and Saglamer, 2003;Bandyopadhyay and Merchant, 2006;Mustafa et al, 2010), snow houses (Dawson, 2002), and urban traffic network (Chen et al, 2005). However, no study exists in the application of the space syntax theory to assess the functional performance of interior spaces such as laboratory facilities.…”
Section: Introductionmentioning
confidence: 99%
“…House floor plans have also been studied in terms of their structures, with an application of graph theory or space syntax. Bandyopadhyay and Merchant (2006) analyzed colonial houses in India and showed that guest rooms tended to be located near an integrated part of the house, whereas sitting rooms located toward a segregated part for secured privacy. Hanazato, Hirano, and Sasaki (2005) analyzed Japanese condominiums and found that a larger dwelling unit had a larger variety of floor plans and its living room tended to be separated from bedrooms, thereby strengthening the independence of bedrooms.…”
mentioning
confidence: 99%